The social network implications of prestigious goods among young adults: evaluating the self vs others. Issue 3 (11th May 2015) - Lee, Seung Hwan; Luster, Sean
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to investigate the paradox of whether prestigious goods help or inhibit a consumer's social affinity. The goal of this research is to explore whether pursuit of prestigious goods increases consumers' social affinity or decreases their social affinity, and, more importantly, to understand the mechanisms that drive this process. Design/methodology/approach – Three laboratory experimental studies and a social network study are conducted to show that consumers hold inconsistent beliefs about the social implication of prestigious goods. Findings – In Study 1, the authors showed that prestigious goods evoked stronger social affinity for the self than for the other. In Study 2, the authors showed that people evaluated themselves high in social affinity when they brought a prestigious wine to a party compared to when they brought a cheaper, generic wine, but evaluated others low in social affinity when they brought the same prestigious wine. In Study 3, the authors showed the mediating effects of social image and boastfulness on social affinity. Study 4 utilizes social network study to further validate previous findings in a field setting. Practical implications – For high-end retailers, the authors suggest framing their promotional messages to explicitly highlight how owning prestigious goods will benefit them (i.e. social image). It is important that these retail managers (and salespeople alike) make it more salient on how their prestigious goods socially benefit the consumer (the self). Thus, it is important to get consumers to think about how a prestigious item looks on them and not on others. However, marketers must be prudent when constructing these messages, as the link between prestigious consumption and network development is merely perceptual. Originality/value – The findings demonstrate that consuming prestigious goods increases social affinity via positive social image for the self. When evaluating others, the authors demonstrate that consuming prestigious goods decreases social affinity via boastfulness. In sum, owning prestigious items may seem beneficial socially to the self, but people have negative perceptions (boastfulness) of those who own the same prestigious goods. Hence, there seems to be a discrepancy in how the authors evaluate themselves versus how they evaluate others with the same prestigious goods.